Real exchange rate adjustment in European transition countries - Maican, Florin G.; Sweeney, Richard J. (Journal of Banking & Finance, 2013)
In single-equation tests, real exchange rates show mean reversion for nine of 10 Central and Eastern European transition countries for the period January 1993 to December 2005. Because of the shift from controlled to market economies and accompanying crises, failed policy regimes and changes in exchange rate regimes, unit root tests for transition countries often require allowance for structural changes. Accounting for structural breaks gives substantially faster mean-reversion speeds than those found for major industrialized countries. These fast adjustment speeds are plausible: Transition countries had perhaps 10years to make unprecedented adjustments required for accession to the European Union. A number of papers have applied non-linear models to the Central and Eastern European countries. This paper investigates four non-linear models and compares them with piece-wise linear break models. The break models appear superior in detecting mean reversion for the Central and Eastern European transition countries.